Men, Women, and Ghosts - Phelps, Elizabeth Stuart, 1844-1911 (Salt Lake City, UT : Project Gutenberg, 2004)
"Men, Women, and Ghosts" by Elizabeth Stuart Phelps is a collection of short stories written during the late 19th century. This work explores themes of love, domestic life, and the struggles of women in a rapidly changing society, often focusing on the complex emotional experiences of its characters. The opening story centers around the wedding of Harrie Bird and Dr. Myron Sharpe, setting the stage for the exploration of their relationship and the challenges they face as they navigate life together. The opening of the collection introduces readers to the idyllic yet complicated beginnings of Harrie's marriage to Dr. Sharpe. The narrator reflects on the wedding ceremony, capturing the joy and hope surrounding the young couple. However, as the narrative unfolds, it hints at the underlying tensions of marital life, especially as they become consumed by the demands of parenthood and societal expectations. The idyllic imagery of their early love contrasts sharply with the reality of their everyday struggles, setting up a tension that invites readers to ponder the complexities of love, ambition, and the roles of men and women in society. (This is an automatically generated summary.)
No news -- The tenth of January -- Night-watches -- The day of my death -- "Little Tommy Tucker" -- One of the elect -- What was the matter? -- In the Gray Goth -- Calico -- Kentucky's ghost.
Release date is 2004-01-01
Produced by Distributed Proofreaders
Keywords: Ghost stories, American; United States -- Social life and customs -- 19th century -- Fiction